Analisis Kepuasan Pelanggan Terhadap Aplikasi Mcdonald’s Dengan Perspektif Pengguna Menggunakan Metode User Experience Questionnaire - Sri Radhitya Murti Mahening; Yopi Handrianto (Informatics and Computer Engineering Journal, 2024)
This study aims to analyze the user satisfaction of the McDonald's application in East Jakarta using the User Experience Questionnaire (UEQ) method. Respondents were asked to fill out the UEQ questionnaire consisting of 26 questions related to six user experience factors, namely attractiveness, perspicuity, efficiency, stimulation, dependability, and novelty. The results of the UEQ analysis show that each user experience variable has an average value above 0.8, indicating positive satisfaction from users of the McDonald's application in East Jakarta. The attractiveness variable obtained a value of (1.421), perspicuity variable (1.445), efficiency variable (1.465), stimulation variable (1.445), dependability variable (1.421), and novelty variable (1.338). This study concludes that the McDonald's application has achieved good results in user satisfaction in East Jakarta, with a positive relationship between attractiveness, clarity, efficiency, stimulation, accuracy, and novelty variables. These findings can be used by McDonald's to enhance the user experience by improving aspects that still need enhancement.